A general auditory bias for handling speaker variability in speech? Evidence in humans and songbirds - Kriengwatana, Buddhamas; Escudero, Paola; Kerkhoven, Anne H.; Cate, Carel ten (Frontiers in Psychology, 2015)
Different speakers produce the same speech sound differently, yet listeners are still able to reliably identify the speech sound. How listeners can adjust their perception to compensate for speaker differences in speech, and whether these compensatory processes are unique only to humans, is still not fully understood. In this study we compare the ability of humans and zebra finches to categorize vowels despite speaker variation in speech in order to test the hypothesis that accommodating speaker and gender differences in isolated vowels can be achieved without prior experience with speaker-related variability. Using a behavioural Go/No-go task and identical stimuli, we compared Australian English adults’ (naïve to Dutch) and zebra finches’ (naïve to human speech) ability to categorize /ɪ/ and /ɛ/ vowels of an novel Dutch speaker after learning to discriminate those vowels from only one other speaker. Experiment 1 and 2 presented vowels of two speakers interspersed or blocked, respectively. Results demonstrate that categorization of vowels is possible without prior exposure to speaker-related variability in speech for zebra finches, and in non-native vowel categories for humans. Therefore, this study is the first to provide evidence for what might be a species-shared auditory bias that may supersede speaker-related information during vowel categorization. It additionally provides behavioural evidence contradicting a prior hypothesis that accommodation of speaker differences is achieved via the use of formant ratios. Therefore, investigations of alternative accounts of vowel normalization that incorporate the possibility of an auditory bias for disregarding inter-speaker variability are warranted.